Disordered Eating Behaviour and Food Addiction among University Students in Lahore, Pakistan - Sultan, Unaiza; Saeed, Ayesha; Ayub, Afia; Ansari, Aliza (International Health Review, 2025)
Disordered Eating Behaviour (DEB) and Food Addiction (FA) are very common among adolescents and young adults across the world. In Pakistan, several studies have been conducted on Eating Disorders (EDs), but data remains scarce regarding DEB and FA. Nutrition students have a better understanding of healthy eating habits than non-nutrition or other students. To assess the prevalence of DEB and FA among nutrition students, allied health sciences students, and general department students, a cross-sectional survey was conducted in June-July 2020. A convenient sample was drawn from three different universities, namely University of South Asia, the University of Lahore, and the University of Veterinary and Animal Sciences, Lahore. A total of 239 participants (185 females and 54 males) volunteered to participate in the study. Two questionnaires (YALE and EAT-26) were employed and distributed through WhatsApp using an online google documents link. Independent sample t-test and ANOVA were employed to observe differences using SPSS 23. A p-value of < 0.05 was taken as significant. The results showed that the mean score of EAT-26 was 15.89 and the mean score of YALE was 4.1. Further, DEB and FA were found to be moderately and positively correlated. Both had a weak positive correlation with weight. Nutrition students had higher EAT-26 scores as compared to the students of other departments. Moreover, DEB and FA were not related to gender. Rather, DEB was found to be more prevalent in nutrition students, although there was no gender difference.